Investigating the effect of an intervention on novice science teachers topic specific pedagogical content knowledge. - Pitjeng, Ramatsobane Judith (My University, 2015)
The lack of teaching experience in uncertified teachers leaves them with little or no understanding of the transformation of Content Knowledge (CK) at their disposal. This transformation of CK is termed Pedagogical Content Knowledge (PCK) and it is known to develop through practice. Therefore, reflective analysis of lessons taught by these teachers is important. Research has also shown that they are often not supported as they embark on their teaching career. Therefore, the study investigated the influence of an intervention on novice unqualified graduate teachers’ (NUGTs) Topic Specific Pedagogical Content Knowledge within a specific topic – the particulate nature of matter. The construct, Topic Specific PCK was the theoretical framework of my study and it consists of five topic specific categories that collectively enable transformation of content knowledge. The categories are: (1) learner prior knowledge (2) curricular Saliency (3) what is difficult to teach (4) representations and (5) conceptual teaching strategies. For measuring the quality of Topic Specific PCK, a new tool based on the topic of the particulate nature of matter was developed. The Topic Specific PCK tool was then validated using a group of 11 practising science teachers. The tool was scored using a rubric that is in line with the five categories, which are rated on a four point scale, where 1 stands for limited PCK and 4 is exemplary PCK. The research design followed in my study was mixed-methods research (MM). The study involved 16 novice teachers recruited by Teach South Africa working together with the Department of Education. The teachers hold university degrees, have done chemistry for a minimum of one year during the course of their degree and have no teaching qualifications. Four of the teachers who taught the particulate nature of matter were selected as case study teachers. Data was collected through a number of tools, including the newly designed Topic Specific PCK test on particulate nature of matter, a CK test and Content Representations (CoRes) which were all adapted from existing tools and thus considered validated. The case study teachers were observed while teaching particulate nature of matter and their lessons were analysed. All the teachers were tested before and after the professional development intervention (PDI). The findings show that the quality of Topic Specific PCK and CK in particulate nature of matter was improved in all NUGTs. The greatest improvement was observed in the NUGTs who taught the topic directly. This improvement was attributed to the experience of teaching the topic directly or teaching related concepts that need understanding of it. The improvement was observed in all the NUGTs, showing the effect of indirect experience. This can be deduced from their improved CoRe which forced the NUGTs to engage with the construct and also through the positive significant improvement in CK and Topic Specific PCK results. Finally, I suggest that although interventions like PDI have the potential to produce science teachers, care should be exercised in making assumptions about their CK and knowledge for teaching, and training programmes need to pay attention to both CK and Topic Specific PCK.
Keywords: Topic specific PCK; Content knowledge; Particulate nature of matter; Transformation of content knowledge